2022
DOI: 10.3389/fcvm.2022.786509
|View full text |Cite
|
Sign up to set email alerts
|

Protective Value of Aspirin Loading Dose on Left Ventricular Remodeling After ST-Elevation Myocardial Infarction

Abstract: AimsLeft ventricular (LV) remodeling after ST-elevation myocardial infarction (STEMI) is a complex process, defined as changes of LV volumes over time. CMR feature tracking analysis (CMR-FT) offers an accurate quantitative assessment of LV wall deformation and myocardial contractile function. This study aimed to evaluate the role of myocardial strain parameters in predicting LV remodeling and to investigate the effect of Aspirin (ASA) dose before primary coronary angioplasty (pPCI) on myocardial injury and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Aspirin is frequently prescribed in the perioperative period of PCI among these drugs. Patients with AMI often receive anti-thrombotic therapy with aspirin at doses of 250–500 mg/kg before PCI ( Calvieri et al, 2022 ). Furthermore, long term use of aspirin is used to prevent secondary myocardial infarction after PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin is frequently prescribed in the perioperative period of PCI among these drugs. Patients with AMI often receive anti-thrombotic therapy with aspirin at doses of 250–500 mg/kg before PCI ( Calvieri et al, 2022 ). Furthermore, long term use of aspirin is used to prevent secondary myocardial infarction after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, drug preconditioning were used to investigate the effect and mechanism of aspirin and gastrodin in myocardial I/R injury. According to equivalent dose conversion between humans and rats, 50 mg/kg aspirin was used for the study ( Huang et al, 2004 ; Calvieri et al, 2022 ). 100 SD rats were randomly divided into two parts.…”
Section: Methodsmentioning
confidence: 99%
“…CMR feature-tracking analysis of LV strain was performed using ventricular short- and long-axis views in cineMR images in a semiautomatic way. LV myocardial tracking was visually reviewed, contouring errors were corrected, and the analysis was repeated as previously described [ 24 , 25 ]. We finally reported the average value of three repeated measurements of global radial (GR-), circumferential (GC-), and longitudinal (GL-) strain (-S) and strain rate (-SR).…”
Section: Methodsmentioning
confidence: 99%
“…Data from the ISIS-2 trial showed unequivocally that aspirin reduces mortality in patients with STEMI but these patients were treated with thrombolysis rather than emergency PCI. It is unlikely that any trial will ever re-examine the efficacy of aspirin in this setting although the differences between the two modes of restoration of vessel patency are considerable ( Calvieri et al, 2022 ). Few studies have looked at dose responses of aspirin in STEMI.…”
Section: Clinical Assessment Of Microvascular Thrombosis During Stemimentioning
confidence: 99%
“…Few studies have looked at dose responses of aspirin in STEMI. One study showed that aspirin loading with 500 mg, compared to 250 mg may further reduce MVO, infarct size and adverse remodelling as assessed by CMR ( Calvieri et al, 2022 ). Furthermore, impaired microcirculatory perfusion after PCI may in part be related to levels of thromboxane B 2 , which is inhibited by aspirin ( Basili et al, 2014 ).…”
Section: Clinical Assessment Of Microvascular Thrombosis During Stemimentioning
confidence: 99%